HINDUISM AND THE RE-HUMANISING OF SOUTH AFRICAN SOCIETY - SOOKLAL, ANIL (Journal for the study of religion, 1993)
South African society is presently in one of the most important periods of its eventful history as it moves towards a democratic non-racial, non-sexist society, freeing itself from the dehumanising forces of apartheid. The religious sector has played a major role in the liberation struggle. However, as the new South Africa begins to unfold, the role of religion in the process of national construction needs to be examined. Religion cannot concern itself solely with matters spiritual. In order to contribute meaningfully to the process of nation-building it has to make a holistic contribution to the creation of a new and just sociopolitical order.